Identifikasi Batuan Dasar menggunakan Metode Seismik Refraksi untuk Pondasi Bangunan di Universitas Sebelas Maret Kentingan Surakarta: Aisyah Yohanella, Budi Legowo, Darsono - Aisyah Yohanella, Aisyah Yohanella; Budi Legowo, Budi Legowo; Darsono, Darsono (Jurnal Fisika dan Aplikasinya, 2025)
Sebelas Maret of University at Kentingan Surakarta in the 2 years period (2011-2012) were doing some construction of buildings such as Pasca Sarjana Building, Nurul Huda Mosque, and the Faculty of Medicine. A building if built on bedrock can reduce the risk of building failure. To be able to determine the presence of bedrock, it can be done by seismic refraction survey method. The survey was conducted in the area of GOR with 4 tracks, field techniques used are in line, with 24 geophones, geophone spacing of 2 meters and 69 meters long track. The data obtained were then processed using software WinSism13 and RockWorks15 for 3D viewing. The results obtained nuanced layers of geological structures in the subsurface based on the value of speed in the medium of propagation or wave propagation speed. From the data processing in the GOR found bedrock to a depth of 27 meters and wave velocity values obtained in rock reach 2000 m/s with constituent rock types are clay rocks.